DERMOSCOPY OF SCABIES - Faruk Alendar; Irdina Drljević; Hana Helppikangas; Temeida Alendar (Our Dermatology Online, 2011)
We presented a female patient a 63 year-old affected with scabies and personal history of previous athropatich psoriasis and arterial hypertension. We aimed to desribed clinically widespread itchy rach vs scabies submited to dermoscopic examination. We confirmed diagnosis of scabies clinically and dermoscopically.